因为p(x1x2=0)=1 ,因为x1x2只有三个值-1,1,0
可知p(x1x2≠0)=0
所以:p(x1x2=1,x1x2=-1)=0
则p(x1=1,x2=1)+p(x1=-1,x2=1)=0
则p(x1=1,x2=1)=p(x1=-1,x2=1)=0
因为p(x2=1)=0.5.所以
p(x1=1,x2=1)+p(x1=-1,x2=1)+p(x1=0,x2=1)=p(x2=1)=0.5
所以p(x1=0,x2=1)=0.5
而p(x1=-1)=p(x1=-1,x2=0)+p(x1=-1,x2=1)=0.25
则p(x1=-1,x2=0)=0.25
p(x1=0)=p(x1=0,x2=0)+p(x1=0,x2=1)=0.5
则p(x1=0,x2=0)=0
p(x1=1)=p(x1=1,x2=0)+p(x1=1,x2=1)=0.25
则p(x1=1,x2=0)=0.25
——————————————————————————————
因为p(x1=1,x2=0)=0.25
而p(x1=1)*p(x2=0)=0
则p(x1=1,x2=0)≠p(x1=1)*p(x2=0)
所以X1X2 不相互独立